2019
DOI: 10.1111/jfpp.14086
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol and eugenol inhibit postharvest soft rot disease by enhancing defense response in peaches during storage

Abstract: Peaches are in high demands because of their nutritional value and delicious flavor, but often become unmarketable due to the fungus infection. In this study, carvacrol and eugenol were used to preserve peaches. Rhizopus stolonifer growth was completely inhibited by carvacrol at 32 µl/Lair and eugenol at 64 µl/Lair. Carvacrol at 0.5 µl/Lair and eugenol at 1 µl/Lair significantly reduced the incidence and severity of soft rot decay in artificially inoculated peaches. Also, carvacrol and eugenol significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…These results indicated that EUG treatment with a high concentration (1.5 %) could stimulate the accumulation of phenolic compounds in inner tissue of FWC. This finding coincided with the results in honey peach reported by Zhou et al (2019) , wherein EUG could activate phenolic metabolism in peach fruit. Given that there was no color change in inner tissue ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…These results indicated that EUG treatment with a high concentration (1.5 %) could stimulate the accumulation of phenolic compounds in inner tissue of FWC. This finding coincided with the results in honey peach reported by Zhou et al (2019) , wherein EUG could activate phenolic metabolism in peach fruit. Given that there was no color change in inner tissue ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…11,12 For example, thyme oil vapors can not only inhibit the growth of fungal pathogens but also enhance fruit disease resistance by increasing the activity of defense-related enzymes, such as phenylalanine ammonia-lyase (PAL), polyphenol oxidase (PPO), peroxidase (POD), chitinase, and β-1,3glucanase (GLU), and regulating metabolism of reactive oxygen species (ROS) in avocados 13,14 and mangoes. 15 Similarly, cinnamaldehyde, 16 carvacrol, and eugenol 17 have been shown to control postharvest diseases by enhancing defense responses in citrus and peach fruits.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, plant essential oils and their constituents used in the food industry have attracted considerable interest due to their broad-spectrum antimicrobial, environmentally friendly, and biodegradable properties, and these oils have been listed in the Generally Regarded as Safe (GRAS) list as food additives by the United States Food and Drug Administration (USFDA). , Various essential oils are effective to control postharvest decay, prolong shelf life, and improve quality of fruits, mainly due to their direct antifungal activity and the induced disease resistance of fruits. , For example, thyme oil vapors can not only inhibit the growth of fungal pathogens but also enhance fruit disease resistance by increasing the activity of defense-related enzymes, such as phenylalanine ammonia-lyase (PAL), polyphenol oxidase (PPO), peroxidase (POD), chitinase, and β-1,3-glucanase (GLU), and regulating metabolism of reactive oxygen species (ROS) in avocados , and mangoes . Similarly, cinnamaldehyde, carvacrol, and eugenol have been shown to control postharvest diseases by enhancing defense responses in citrus and peach fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable rot is a common phenomenon in the process of crop cultivation, transportation, and storage, leading to vast economic loss and food waste annually . Plant rotting diseases are generally caused by fungi or bacteria. , Among all these notorious microorganisms, Pectobacterium carotovorum is one of the most pathogenic strains . It induces soft rot of tissues and organs of various plants, including potato, lettuce, celery, and Brassicaceae leafy vegetables .…”
Section: Introductionmentioning
confidence: 99%
“…2 Plant rotting diseases are generally caused by fungi or bacteria. 3,4 Among all these notorious microorganisms, Pectobacterium carotovorum is one of the most pathogenic strains. 5 It induces soft rot of tissues and organs of various plants, including potato, lettuce, celery, and Brassicaceae leafy vegetables.…”
Section: ■ Introductionmentioning
confidence: 99%